Multiparty Access Control and Content Based Filtering for Online Social Networks (International Journal of Engineering and Computer Science, 2015)
Today the social network is that the most significant space to the users to connect with every other .it provides a lot of facility to the users and conjointly a lot of drawbacks for users. it's seen tremendous growth in on-line in recent years in social networks. These OSNs aren't solely engaging for data sharing and virtual social interactions, however jointly raise privacy problems and variety of security. though OSNs enable one user to get access the information, they presently don't give any mechanism to enforce privacy issues over information data multiple users. The remaining privacy violations for the most part unresolved and resulting in the potential revealing of knowledge, that at least one user supposed to stay non-public. during this paper, propose AN approach to change cooperative privacy management of shared information in OSNs. specifically, give a scientific mechanism to spot and resolve privacy conflicts for cooperative data sharing. The conflict resolution indicates a trade-off between privacy protection and information sharing by quantifying privacy risk and sharing loss. And conjointly mentioned a proof-of-concept prototype implementation of approach as a region of an application in Face book and supply system analysis and value study of our methodology.